Pattern of skin bacteria in palmar arsenical keratosis (Bangladesh Journal of Pharmacology, 2016)
The aim of the present study was to examine the involvement of skin bacteria in the pathogenesis of keratosis. Skin swab of five different sites (palm, dorsum of the hand, chest, axilla and alar crease) from arsenic unexposed volunteer (n = 15), arsenic exposed (n = 15) and arsenicosis patients (n= 20) were collected for bacterial culture. The skin of arsenic unexposed volunteers contained Staphylococcus epidermidis and Bacillus spp. Chronic exposure to high concentration of arsenic through drinking water altered the skin bacterial pattern. The growth of Pseudomonas spp. increased in different sites of the skin. But in patient of arsenicosis, the skin of the palm shows the growth of Enterobacter spp.